2023
DOI: 10.1039/d3dt02056h
|View full text |Cite
|
Sign up to set email alerts
|

Structural diversity in proline-based lead bromide chiral perovskites

Abstract: Lead halide hybrid perovskites incorporating chiral organic cations attract considerable attention due to their promising application in multifarious optoelectronic devices. However, the examples of chiral hybrid perovskites are still limited...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
0
0
Order By: Relevance
“…At present, there have been many studies of the structure–property relationship of lead-based halide perovskite luminescent materials. Research has shown that different connection modes of octahedra result in different dimensional configurations, , as well as varying degrees of distortion of octahedra, which are factors affecting the luminescence properties of lead-based halide perovskites. Compared with that of lead-based halide perovskites, the structure–property relationship of copper­(I)-based halides has received less attention, and these studies are relatively isolated.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there have been many studies of the structure–property relationship of lead-based halide perovskite luminescent materials. Research has shown that different connection modes of octahedra result in different dimensional configurations, , as well as varying degrees of distortion of octahedra, which are factors affecting the luminescence properties of lead-based halide perovskites. Compared with that of lead-based halide perovskites, the structure–property relationship of copper­(I)-based halides has received less attention, and these studies are relatively isolated.…”
Section: Introductionmentioning
confidence: 99%